Государственное регулирование в энергетике - Домбровская, Г. П.; Бубенко, И. В. (НТУ "ХПИ", 2010)
Досліджено методологічні аспекти формування і функціонування конкурентного оптового ринку електроенергії і обґрунтована необхідність переходу від державного регулювання до конкурентного електроенергетичного ринку. Досліджено моделі формування тарифів конкурентного оптового ринку електроенергії на основі концепції граничних витрат.

The methodological aspects of forming and functioning of competition wholesale market of electric power are investigational and a transition necessity is grounded from government control to the competition electroenergy market. The models of forming of tariffs of competition wholesale market of electric power are investigational on the basis of conception of maximum expenses.
Keywords: топливно-энергетический комплекс; энергетическое обследование; рынок электроэнергии; коммерческий учет; перспективные тарифы; концепция предельных затрат